2016
DOI: 10.7566/jpsj.85.124004
|View full text |Cite
|
Sign up to set email alerts
|

Are Quasiparticles and Phonons Identical in Bose–Einstein Condensates?

Abstract: We study an interacting spinless Bose-Einstein condensate to clarify theoretically whether the spectra of its quasiparticles (one-particle excitations) and collective modes (two-particle excitations) are identical, as concluded by Gavoret and Nozières [Ann. Phys. 28, 349 (1964)]. We derive analytic expressions for their first and second moments so as to extend the Bijl-Feynman formula for the peak of the collective-mode spectrum to its width (inverse lifetime) and also to the one-particle channel. The obtained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
(74 reference statements)
2
11
0
Order By: Relevance
“…Thus, the result here also supports (i ′ ), as does our previous study. 15 The finite lifetime of non-condensed particles may be regarded as a crucial element for realizing and sustaining temporal coherence in the condensate. This paper is organized as follows.…”
Section: Fig 1: Classification Of Collision Processes In Homogeneousmentioning
confidence: 99%
“…Thus, the result here also supports (i ′ ), as does our previous study. 15 The finite lifetime of non-condensed particles may be regarded as a crucial element for realizing and sustaining temporal coherence in the condensate. This paper is organized as follows.…”
Section: Fig 1: Classification Of Collision Processes In Homogeneousmentioning
confidence: 99%
“…The ultracold atomic gases may also serve as an ideal potential platform for directly addressing the strong connection between the single-particle excitation and the density excitation in BECs. On the other hand, several theories have been proposed that cast doubt on the paradigm about the BEC [25][26][27][28][29][30][31]: the correspondence between the single-particle excitation and the collective excitation in the low-energy and low-momentum region.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our finitetemperature analysis in terms of discrete Matsubara frequencies, where the frequency renormalization factor B becomes irrelevant, indicates clearly that the Bogoliubov dispersion should be absent at least at finite temperatures for d ≤ 4. Moreover, the argument on the persistence of the linear dispersion by Nepomnyashchi ȋ and Nepomnyashchi ȋ39,40 is implicitly based on the Gavoret-Nozières result 6 that the one-and two-particle Green's functions share a common pole, whose validity we have been questioning; 43,44 see also the second paragraph below on this point. Instead, we here argue that no branch with a linear dispersion exists in the one-particle channel at T > 0 for d ≤ 4.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Indeed, it was shown that, when applied to Bose-Einstein condensates, the two distinct proofs are relevant to the poles of one-and two-particle Green's functions, 43 respectively, which are not necessarily identical. 44 The work by Watanabe and Murayama 16 on Goldstone's theorem (II) predicts a single Nambu-Goldstone mode in the two-particle channel with a linear dispersion relation ∝ k for k → 0. On the other hand, the present study relevant to the one-particle channel predicts no modes with a linear dispersion below d c = 4 (d c = 3) at finite temperatures (zero temperature).…”
Section: Introductionmentioning
confidence: 99%